A new species of Landrevinae (Orthoptera) from the Philippines, with notes on Endodrelanva and Endolandrevus (Orthoptera: Gryllidae; Gryllinae; Landrevini) - Tan, Ming Kai; Gorochov, Andrej V.; Baroga-Barbecho, Jessica B.; Yap, Sheryl A. (Zootaxa, 2019)
Owing to the cryptic behavior and morphology of many Southeast Asian Landrevinae, new species are still being discovered in unexplored parts of the region. Here, we describe a new species: Endodrelanva siargaoensis sp. nov. We also recorded and describe the calling song of the new species. Owing to the morphological similarities between species of Endodrelanva Gorochov, 2000 and Endolandrevus Saussure, 1877, we also provide a short review of the two genera and list their characters for comparison.